In vitro antibacterial activity and essential oil composition of Litsea petiolata Hook. f. leaves - Patumporn Thongthip, Piyamas Atiphasaworn, Sakon Monggoot, Acharavadee Pansanit & , Patcharee Pripdeevech & (Journal of Applied Pharmaceutical Science, 2017)
Essential oil of Litsea petiolata (Hook f) was extracted from their leaves collecting from Chiang Rai province, Northern Thailand. Hydrodistillation technique with Clevenger system was performed to extract L. petiolata essential oil. The essential oil composition was further analyzed by gas chromatographic-mass spectrometric technique. A total of 74 volatile constituents were identified. Representing 96.94% of the oil with 2-ketonesare the key compound group. The major identified volatile components were 2-undecanone (79.52%) , 12-tridecen-2-one (6.26%) and 2-nonanone (2.46%) , respectively. The essential oil of L. petiolata (Hook f) leaves showed good antibacterial activity against tested Gram-positive and Gram-negative human pathogenic bacteria including Bacillus cereus ATCC 11778, B. subtilis TISTR 008, Staphylococcus aureus ATCC 25923, S. epidermidis ATCC 12228, S. agalactiae DMST 17129, Escherichia coli ATCC 25922, Salmonella typhimurium ATCC 13311, Vibrio cholerae DMST 2873 and V. parahaemolyticus DMST 21243. The zone of inhibition was obtained from9.54±1.24 to 18.07±2.19 mm. The minimum inhibitory concentration (MIC) values were within the antibacterial activity range and varied between 31.25 and 500 μg/mL. The essential oil of L. petiolata (Hook f) leaves showed maximum antibacterial activity against S. aureus ATCC 25923 and E. coli ATCC 25922. This study indicates that L. petiolata (Hook f) leaf oil could be employed as a natural medicinal application in antibacterial drugs.
Keywords: Litsea petiolata (Hook f), essential oil, antibacterial, composition, GC-MS.